Pomen teoretičnih modelov za sodobno zdravstveno nego - Hajdinjak, Angela (Obzornik zdravstvene nege, 1999)
The article describes basic differences between traditional and modern nursingcare and presents basic elements of nursing care with special stress ontheoretical models which are of specific importance for the profession, and some groups of theoretical models grouped according to their contents.
Keywords: modeli; Models, nursing; Nursing care; Nursing theory; zdravstvena nega